A Tailorable Family of Elastomeric‐to‐Rigid, 3D Printable, Interbonding Polymer Networks. (19th May 2020) - Zhou, Qing; Gardea, Frank; Sang, Zhen; Lee, Seunghyun; Pharr, Matt; Sukhishvili, Svetlana A.
Abstract: Soft materials with widely tailorable mechanical properties throughout the material's volume can shape the future of soft robotics and wearable electronics, impacting both consumer and defense sectors. Herein, a platform of 3D printable soft polymer networks with unprecedented tunability of stiffness of nearly three orders of magnitude (MPa to GPa) and an inherent capability to interbond is reported. The materials are based on dynamic covalent polymer networks with variable density of crosslinkers attached to prepolymer backbones via a temperature‐reversible Diels–Alder (DA) reaction. Inherent flexibility of the prepolymer chains and controllable crosslinking density enable 3D printed networks with glass transition temperatures ranging from just a few degrees to several tens of degrees Celsius. Materials with an elastomeric network demonstrate a fast and spontaneous self‐healing behavior at room temperature both in air and under water—a behavior difficult to achieve with other crosslinked materials. Reversible dissociation of DA networks at temperatures exceeding ≈120 °C allows for reprintability, while control of the stereochemistry of DA attachments enables reprogrammable shape memory behavior. The introduced platform addresses current major challenges including control of polymer interbonding, enhanced mechanical performance of printed parts, and reprocessability of 3D‐printed crosslinked materials in the absence of solvent. Abstract : A family of reversibly crosslinked polymer networks with wide‐ranging mechanical properties is developed. The materials are highly suitable for use with facile 3D printing techniques, seamlessly bond in spite of mismatch in stiffness, can autonomously self‐heal in air and underwater at room temperature, and enable reprogramming their shape through plastic deformation of the network.